Mapping and evaluating national data flows: transparency, privacy, and guiding infrastructural transformation - Joe Zhang, BMBCh; Jess Morley, MS; Jack Gallifant, MSc; Chris Oddy, MBBS; James T Teo, ProfPhD; Hutan Ashrafian, ProfPhD; Brendan Delaney, ProfPhD; Ara Darzi, ProfPhD (The Lancet: Digital Health, 2023)
Summary: The importance of big health data is recognised worldwide. Most UK National Health Service (NHS) care interactions are recorded in electronic health records, resulting in an unmatched potential for population-level datasets. However, policy reviews have highlighted challenges from a complex data-sharing landscape relating to transparency, privacy, and analysis capabilities. In response, we used public information sources to map all electronic patient data flows across England, from providers to more than 460 subsequent academic, commercial, and public data consumers. Although NHS data support a global research ecosystem, we found that multistage data flow chains limit transparency and risk public trust, most data interactions do not fulfil recommended best practices for safe data access, and existing infrastructure produces aggregation of duplicate data assets, thus limiting diversity of data and added value to end users. We provide recommendations to support data infrastructure transformation and have produced a website (https://DataInsights.uk) to promote transparency and showcase NHS data assets.